Cross-Species RNA-Seq Study Comparing Transcriptomes of Enriched Osteocyte Populations in the Tibia and Skull - Wang, Ning; Niger, Corinne; Li, Nan; Richards, Gareth O.; Skerry, Tim M. (Frontiers in Endocrinology, 2020)
Local site-specific differences between bones in different regions of the skeleton account for their different properties and functions. To identify mechanisms behind these differences, we have performed a cross-species study comparing RNA transcriptomes of cranial and tibial osteocytes, from bones with very different primary functions and physiological responses, collected from the same individual mouse, rat and rhesus macaque. Bioinformatic analysis was performed to identify 32 genes changed in the same direction between sites and shared across all three species. Several well-established key genes in bone growth and remodelling were upregulated in the tibias of all three species (BMP7, DKK1, FGF1, FRZB, SOST). Many of them associate or crosstalk with the Wnt signalling pathway. These results suggest Wnt signalling-related candidates for different control of regulatory mechanisms in bone homeostasis in the skull and tibia and indicate a different balance between genetically determined structure and feedback mechanisms to strains induced by mechanical loading at the different sites.